Power and Ownership Structures among German Companies. A Network Analysis of Financial Linkages - Jochen Moebert; Patrick Tydecks (Technische Universität Darmstadt, Department of Law and Economics, 2007)
The literature on ownership structures made continual use of notions such as cross-holdings and pyramids which are closely related to the vastly increasing network literature. We propose to transfer successfully applied network methods to the corporate control and corporate governance branch as well. For instance, in this paper we use the MAN-classification scheme, centrality concepts, and network graphs to investigate a unique data set containing 2784 companies of the ownership structure in Germany in 2006. Furthermore, the power or centrality of companies is explained by various company variables.
Keywords: G32; L14; 330; network; ownership structure; corporate control; power; financial linkages; Eigentümerstruktur; Business Network; Wirtschaftskonzentration; Wirtschaftliche Macht; Deutschland